2011
DOI: 10.1186/1743-422x-8-420
|View full text |Cite
|
Sign up to set email alerts
|

True prevalence of twin HDV-HBV infection in Pakistan: a molecular approach

Abstract: Hepatitis Delta Virus (HDV) infects only patients that are already infected by hepatitis B virus (HBV) because this is sub satellite virus which depends on and propagate only in the presence of HBV. HDV causes co-infection or super infection with sever complication as compared to only HBV infection. No study on molecular level on HDV is available from this region; therefore, the aim of this study was to found out the molecular epidemiology of HDV (as a co-infection with HBV) in different geographical regions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
21
3

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 15 publications
6
21
3
Order By: Relevance
“…In contrast to ours and other Iranian studies, they found a different HDV risk between both genders as 0.36 times less in women and concluded that it may be due to greater rate of high risk behaviors in men (22). Similar to the study of Zahedan, in Pakistan (eastern neighbor of Sistan and Balouchestan province), Khan et al (23) reported a rate of 28% for HDV and indicated a significantly higher rate of HDV among male patients, but regarding to age, no significant difference was seen in patients with ages above or below 40 years. Another study from Pakistan (24) found that 31.5% of their patients were anti-HDV positive and no significant difference was found between positive and negative groups regarding to age, gender, marital status, and place of residence.…”
Section: Discussionsupporting
confidence: 63%
“…In contrast to ours and other Iranian studies, they found a different HDV risk between both genders as 0.36 times less in women and concluded that it may be due to greater rate of high risk behaviors in men (22). Similar to the study of Zahedan, in Pakistan (eastern neighbor of Sistan and Balouchestan province), Khan et al (23) reported a rate of 28% for HDV and indicated a significantly higher rate of HDV among male patients, but regarding to age, no significant difference was seen in patients with ages above or below 40 years. Another study from Pakistan (24) found that 31.5% of their patients were anti-HDV positive and no significant difference was found between positive and negative groups regarding to age, gender, marital status, and place of residence.…”
Section: Discussionsupporting
confidence: 63%
“…The PCR program was as follows: 5 min at 95°C; 35 cycles of 1 min at 95°C, 1 min at 64°C, and 1 min at 72°C; and 10 min at 72°C. The expected size of the PCR product was 592 bp (11). No HDV RNA was detected in any of the three specimens.…”
mentioning
confidence: 93%
“…This situation might be explained by the high frequency of co-infection HDV/HBV in both populations. Patients between 30 and 40 years were most concerned about HDV infection in Nigeria but differ with the findings observed in Pakistan (Khan et al, 2011). This difference could be explained by the characteristics of the populations in different study particularly differences in proportions of the various categories of HBV and/or different study population profiles.…”
Section: Discussionmentioning
confidence: 66%